Semantic Categorization of Placement Verbs in L1 and L2 Danish and Spanish. Issue 1 (28th October 2015) - Cadierno, Teresa; Ibarretxe‐Antuñano, Iraide; Hijazo‐Gascón, Alberto
Abstract : This study investigates sematic categorization of the meaning of placement verbs by Danish and Spanish native speakers and two groups of intermediate second language (L2) learners (Danish learners of L2 Spanish and Spanish learners of L2 Danish). Participants described 31 video clips picturing different types of placement events. Cluster analyses revealed considerable differences in the semantic categorization of these events in Danish and Spanish as well as learning difficulties for the two learner groups. When Danish and Spanish differ in the number and nature of semantic distinctions, L2 verb meaning reconstruction becomes challenging when moving from a more to a less complex system and vice versa. Both learner groups used noncaused motion verbs, overgeneralized given placement verbs, and tended to use L2 verbs haphazardly.